Transformation of Rambu Solo’ Rituals and Toraja Cultural Identity in Global Tourism: A Literature Review (2010–2025) - Aswar, Aswar; Assidiq, Fauziah Ramadhany; Tajuddin, Fatjri Nur (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study systematically reviews 45 articles published between 2010 and 2025 to examine the transformation of the Rambu Solo’ funeral ceremony in Tana Toraja from a sacred ritual to a cultural tourism commodity. The objectives are to analyze shifts in ritual function, evaluate socio-economic impacts on local families, and identify cultural preservation strategies employed by the Toraja community. Using a qualitative approach with Systematic Literature Review (SLR) and thematic analysis, the study synthesizes patterns of ritual adaptation, cultural commodification, identity negotiation, and community-based preservation initiatives. Findings reveal that Rambu Solo’ now serves both spiritual and socio-economic purposes, with tourism generating income and cultural pride but also creating financial pressures and social competition. Community-based tourism, cultural festivals, educational programs, and heritage documentation are employed to maintain the sacred essence of rituals while adapting to global economic realities. The study underscores the novelty of empowering local communities to curate their cultural narratives, balancing authenticity and economic pragmatism. These insights provide guidance for sustainable cultural tourism development that preserves Toraja’s spiritual and social identity amidst globalization.